Transfer Pricing and Tax Planning Analysis of the Effectiveness of the Gross-Up Method and Its Implications for Equity of Income Distribution - Cahyoginarti Cahyoginarti; Rehulina Bangun; Benhur Pakpahan; Sabarita Tarigan (International Journal of Economics, Management and Accounting, 2025)
Economic globalization has increased the complexity of cross-border transactions, particularly in transfer pricing practices, which are often used by multinational companies to shift profits to lower-tax jurisdictions. While this strategy can legally reduce tax burdens, aggressive transfer pricing often leads to income distribution inequalities and reduced government tax revenues. On the other hand, tax planning using the Gross-Up method in Article 21 Income Tax has emerged as a more transparent alternative strategy that enhances employee welfare through company-covered tax incentives. This study analyzes the effectiveness of the Gross-Up method in managing tax obligations and its impact on economic fairness compared to transfer pricing practices. Using a qualitative approach based on case studies of companies in Indonesia, the study finds that implementing the Gross-Up method can improve tax compliance and employee loyalty, whereas uncontrolled transfer pricing poses a risk of reducing government tax revenues. Therefore, stricter and more transparent tax regulations are needed to mitigate the misuse of transfer pricing and encourage the adoption of fairer tax planning strategies.